Economic analysis of animal genetic resources and the use of rural appraisal methods: lessons from Southeast Mexico - Drucker, Adam G.; Anderson, S. (2004)
Livestock diversity provides genetic alternatives that facilitate sustainable agricultural development. Despite this, animal genetic resources (AnGR) are being depleted at alarming rates. Subsidises available to production systems based on imported breeds are of several orders of magnitude greater than the costs of local breed conservation. Economic arguments for the conservation and sustainable use of threatened AnGR can be an effective means of establishing support for the development of appropriate enabling environments. Despite the importance of the economics of AnGR conservation, the subject has received limited attention. Reasons include: methodological difficulties inherent in valuing genetic resources; limited knowledge about appropriate analytical techniques; and lack of data regarding local breeds. As recent advances in economic valuation have eased methodological/analytical constraints, the issue of data availability has become critical. Data related to livestock keepers' preferences for different genetic resource attributes and the value placed on these across species, breeds and production systems are needed. Based on a study of a local pig breed in Mexico, this paper shows how the use of rural appraisal methods, in conjunction with recently developed analytical techniques, are capable of providing the data required for understanding the type and costs of interventions necessary to promote the conservation and sustainable use of AnGR.